Persepsi Penyuluh Agama Islam terhadap Program Pendirian Kampung Zakat di Mandailing Natal - Lubis, Nurfauzy (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2024)
Improving society’s quality of life is one of ideas in emergence of Zakat Village Program. Zakat Village Program which has been launched by the Indonesian Ministry of Religion must be realized on a macro and micro scale, including in Mandailing Natal Regency. This program cannot be separated from the active participation and involvement of Islamic religious instructors as religious guides. The implementation of Zakat Village Program is measured by the readiness of Islamic religious instructors to make this happen. The ideas that develop must accordance with the ideas held by Islamic religious instructors, including their perceptions of village zakat program. Research aims to determine and analyze the perceptions of Islamic religious instructors regarding Zakat Village establishment program in Mandailing Natal Regency. This research is descriptive research with a quantitative approach. Data collection techniques were using observation, distributing questionnaires to 216 Islamic religious instructors and documentation. The results show that according cognitive aspect, Islamic religious instructors already have knowledge about zakat villages and wish to establish one in Mandailing Natal with a percentage of 66.5% or in high category. In affective aspect, feeling of being involved in establishing zakat village was rated high with percentage 70.6%. In conative aspect, Islamic religious instructors are participate actively. They will campaign for this program. This aspect has a percentage 64% or high category.